Biomaterials-Mediated Tumor Infarction Therapy - Tong, Shizheng; Zhao, Wei; Zhao, Duoyi; Zhang, Weilin; Zhang, Zhiyu (Frontiers in Bioengineering and Biotechnology, 2022)
Agents for tumor vascular infarction are recently developed therapeutic agents for the vascular destruction of tumors. They can suppress the progression of the tumor by preventing the flow of nutrition and oxygen to its tissues. Agents of tumor vascular infarction can be divided into three categories according to the differences in their pathways of action: those that use the thrombin-activating pathway, fibrin-activating pathway, and platelet-activating pathway. However, poor targeting ability, low permeation, and potential side-effects restrict the development of the corresponding drugs. Biomaterials can subtly avoid these drawbacks to suppress the tumor. In this article, the authors summarize currently used biomaterials for tumor infarction therapy with the goal of identifying its mechanism, and discuss outstanding deficiencies in methods of this kind.